Smartphone-based photoplethysmographic imaging for heart rate monitoring. (4th July 2017) - Alafeef, Maha
Abstract: The purpose of this study is to make use of visible light reflected mode photoplethysmographic (PPG) imaging for heart rate (HR) monitoring via smartphones. The system uses the built-in camera feature in mobile phones to capture video from the subject's index fingertip. The video is processed, and then the PPG signal resulting from the video stream processing is used to calculate the subject's heart rate. Records from 19 subjects were used to evaluate the system's performance. The HR values obtained by the proposed method were compared with the actual HR. The obtained results show an accuracy of 99.7% and a maximum absolute error of 0.4 beats/min where most of the absolute errors lay in the range of 0.04–0.3 beats/min. Given the encouraging results, this type of HR measurement can be adopted with great benefit, especially in the conditions of personal use or home-based care. The proposed method represents an efficient portable solution for HR accurate detection and recording.